Como se essas palavras estivessem pegando fogo também: caça às bruxas como disparador poético para um caminho sonoro-dramatúrgico - Camuça, Nádia da Silva (2024)
This work presents the path of an artistic investigation using the work Caliban and the Witch (2017), by Silvia Federici, as a poetic trigger in the creation of a dramaturgy in the format of an audiowalk. Thus, based on her observations, I searched to create a scenic material thinking about and with the voices, stories and knowledge of the witches who suffered an attempted annihilation during the period of the witch hunt. In this research, I am also inspired by the texts of Gloria Anzaldúa - when she speaks of her wild and untamed language as a Chicana poet; and Hélène Cixous wich reconstructs the myth of Medusa - a woman with a hair made of tongues that were cut off. Finally, I present experiments in audiowalk, having found in this format a dramaturgical proposal that unites the diverse interests of this research: the city, the voices, the sounds and thus thinking about the figure of the witch as this symbol of female resistance and rebellion, with a language that even after being thrown into the fire continues to dance in our ears.